PENGARUH MODAL, LAMA USAHA, TEKNOLOGI TERHADAP PRODUKTIVITAS TENAGA KERJA DAN PENDAPATAN UMKM DI DENPASAR UTARA - Putra, I Putu Adi Subaktha; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 10 (2020): VOL 9 NO 10, OKTOBER 2020 (2152 - 2389), 2020)
Micro, Small and Medium Enterprises in Indonesia is one of the priorities in the development of the national economy. The objectives of this study are (1) to analyze the effect of capital, business duration, and technology on the productivity of UMKM workers in the District of North Denpasar; (2) to analyze the effect of capital, business duration, technology and labor productivity on UMKM income in the District of North Denpasar; (3) to analyze the indirect effect of capital, business duration and technology on UMKM income through labor productivity. This research was conducted in the District of North Denpasar with a sample of 120 UMKM. The sampling method is proportionate stratified random sampling. The analysis technique used is the path analysis technique (path analysis). The results showed that, 1) capital, business duration and technology had a positive and significant effect on labor productivity at UMKM in Denpasar City, 2) capital, business duration, technology and labor productivity had a positive and significant effect on MSME income at UMKM in the City Denpasar, 3) capital, business duration and technology at UMKM in Denpasar City indirectly affect UMKM income through labor productivity. Keywords: capital, business duration, technology, labor productivity, MSME income.